LNG in Transition: from uncertainty to uncertainty - Bassam Fattouh; David Ledesma (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2019)
The September 2019 issue of the Oxford Energy Forum looks at the uncertainties facing the LNG sector as it transitions from its traditional rigid structure to becoming a fully traded commodity. This change is happening during a period of considerable volume growth in the industry, with LNG supply expected to double between 2016 and 2020. In four sections, the publication examines the uncertainties facing LNG demand and supply, how LNG pricing structures are evolving and the growth in LNG trading, before discussing LNG shipping, plant costs and the evolution of floating liquefaction.~ Through twelve articles, this issue has a common theme running through it – one of uncertainty, be it over the level of demand or supply, or the pace of technological advancement along the value chain, and examines potential outcomes and where the LNG transition could end up.
Keywords: 330